High Therapeutic Efficiency of Magnetic Hyperthermia in Xenograft Models Achieved with Moderate Temperature Dosages in the Tumor Area - Kossatz, Susanne (Pharm Res, 2014)
PURPOSE: Tumor cells can be effectively inactivated by heating mediated by magnetic nanoparticles. However, optimized nanomaterials to supply thermal stress inside the tumor remain to be identified. The present study investigates the therapeutic effects of magnetic hyperthermia induced by superparamagnetic iron oxide nanoparticles on breast (MDA-MB-231) and pancreatic cancer (BxPC-3) xenografts in mice in vivo. METHODS: Superparamagnetic iron oxide nanoparticles, synthesized either via an aqueous (MF66; average core size 12 nm) or an organic route (OD15; average core size 15 nm) are analyzed in terms of their specific absorption rate (SAR), cell uptake and their effectivity in in vivo hyperthermia treatment. RESULTS: Exceptionally high SAR values ranging from 658 ± 53 W*g(Fe) (−1) for OD15 up to 900 ± 22 W*g(Fe) (−1) for MF66 were determined in an alternating magnetic field (AMF, H = 15.4 kA*m(−1) (19 mT), f = 435 kHz). Conversion of SAR values into system-independent intrinsic loss power (ILP, 6.4 ± 0.5 nH*m(2)*kg(−1) (OD15) and 8.7 ± 0.2 nH*m(2)*kg(−1) (MF66)) confirmed the markedly high heating potential compared to recently published data. Magnetic hyperthermia after intratumoral nanoparticle injection results in dramatically reduced tumor volume in both cancer models, although the applied temperature dosages measured as CEM43T90 (cumulative equivalent minutes at 43°C) are only between 1 and 24 min. Histological analysis of magnetic hyperthermia treated tumor tissue exhibit alterations in cell viability (apoptosis and necrosis) and show a decreased cell proliferation. CONCLUSIONS: Concluding, the studied magnetic nanoparticles lead to extensive cell death in human tumor xenografts and are considered suitable platforms for future hyperthermic studies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11095-014-1417-0) contains supplementary material, which is available to authorized users.